The Origin of Observed Magnetic Variability for a Sol on Mars From InSight. Issue 9 (21st September 2020) - Mittelholz, A.; Johnson, C. L.; Thorne, S. N.; Joy, S.; Barrett, E.; Fillingim, M. O.; Forget, F.; Langlais, B.; Russell, C. T.; Spiga, A.; Smrekar, S.; Banerdt, W. B.
Abstract: Day‐night variations in the magnetic field at Mars have been previously observed at satellite altitudes. The InSight Fluxgate Magnetometer (IFG) has provided the first evidence for diurnal magnetic field variations at the martian surface. IFG data show diurnal variations with typical peak amplitudes of 20–40nT in the early morning to midmorning; the amplitude of the magnetic field varies over the first 389 sols of the mission and peaks between sols 50 and 100. Temperature variations, solar array currents, and lander activities all generate magnetic fields. Particularly, the first two of these also produce signals with clear diurnal variations. We first assess the IFG data calibration and conclude that temperature and solar array currents have only minimal effects on the variability we observe in the final calibrated magnetic field data. We use satellite magnetic field data and a Mars global circulation model to make predictions for the temporal evolution of wind‐driven fields in the ionosphere. Such fields vary due to seasonal changes in the ionization profile and the winds, and in the altitude range of the dynamo region, that is, the region in which electric currents can be produced. We find that the amplitude and seasonal variability of the surface magnetic fields are generally consistent with those predicted from wind‐driven currents. Moreover, a regional dust storm in the vicinity of the InSight landing site, which started around sol 45, might be responsible for the higher magnetic field amplitudes observed in the IFG data in the early part of the mission. Plain Language Summary: The InSight lander carries a magnetometer, which has for the first time measured magnetic fields on the surface of Mars. The observed magnetic field strength varies from day to night and peaks in the early morning to midmorning. We report how these diurnal variations have evolved over the first 389 sols (martian days) of the InSight mission and show that there are substantial sol‐to‐sol changes as well as more gradual changes over longer timescales. We investigate whether these are caused by the diurnal variations in temperature of the magnetometer instrument and the electronics box, day‐night‐variations in the currents drawn from the lander's solar arrays, and lander activities such as movement of the arm and satellite communications. We conclude that these sources are generally well accounted for in the processed magnetometer data. We then investigate whether the diurnal variations in the field could be caused by charged particles in the upper atmosphere (ionosphere) that move with the wind and generate electric currents. We model this process using a climate model for Mars and find that the predicted magnetic fields are consistent with the observed evolving diurnal pattern. This indicates that at least some of the magnetic field variability on ground is indeed generated in the ionosphere. Key Points: InSight magnetometer data for sols 14–389 show diurnal magnetic field variations The field strength consistently peaks in the early morning to midmorning, with typical amplitudes of 20–40 nT but can reach almost 80 nT Wind‐driven ionospheric currents predict some of the observed signal, including the increased amplitude during a regional dust storm